Prevalence and determinants of anemia in chronic kidney disease patients in Ethiopia: a systematic review and meta-analysis - Eshetu Elfios Endrias; Temesgen Geta; Eskinder Israel; Melesse Belayneh Yayeh; Beker Ahmed; Abdulkerim Hassen Moloro (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease (CKD) is a progressive and devastating condition affecting over 10% of the global population, with more than 800 million individuals impacted worldwide. Anemia, a critical and debilitating complication of CKD, accelerates disease progression and exacerbates its overall burden. Despite numerous studies exploring the prevalence and determinants of anemia in CKD in Ethiopia, the pooled prevalence remains undefined, highlighting a critical gap in evidence.ObjectivesTo determine the pooled prevalence of anemia and identify its associated factors among CKD patients in Ethiopia through a systematic review and meta-analysis.MethodsA comprehensive search was carried out for studies with full document and written in English language through an electronic web-based search strategy from databases of PubMed, CINAHL, Cochrane Library, Embase, Google Scholar and Ethiopian University Repository online. The quality of the included studies was assessed using the Joanna Briggs Institute (JBI) checklist. Statistical analyses were performed using STATA version 17. Meta-analysis was conducted with a random-effects model. Heterogeneity among the primary studies was evaluated using Cochran’s Q test and the I-squared statistic. To explore potential sources of heterogeneity, subgroup and sensitivity analyses were performed.ResultsThis systematic review and meta-analysis included seven studies, involving a total of 1,714 CKD patients. The pooled prevalence of anemia among CKD patients was 60.93% (95% CI: 50.05, 71.80), with substantial heterogeneity observed across studies (I2 = 97.0, P < 0.000). A significant association was found between anemia in CKD patients and diabetes comorbidity, with those having diabetes experiencing significantly higher odds of developing anemia (OR: 4.52, 95% CI: 1.18–7.28). Additionally, patients in stage 3 or more advanced stages of CKD had an increased risk of anemia (OR: 4.36, 95% CI: 3.15–5.57).Conclusion and recommendationsThis systematic review and meta-analysis revealed a high pooled prevalence of anemia among CKD patients, with significant associations with diabetes mellitus comorbidity, and advanced CKD stages. Regional differences were also noted, with Oromia region showing the highest prevalence. We recommend regular anemia screening in CKD patients and the identification and management of risk factors such as diabetes and advanced CKD stages.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024608561, identifier CRD42024608561.